Covert research and adult protection and safeguarding: an ethical dilemma?. Issue 1 (2014) - ,; ,
Abstract : Purpose – This paper aims to consider the contentious issue of covert research in studying the social contexts of vulnerable groups. It explores its potential utility in areas where overt strategies may be problematic or denied; and examines and problematises the issue of participant consent.Design/methodology/approach – Using a literature‐based review and selected previous studies, the paper explores the uses and abuses of covert research in relation to ethics review proceedings governing social research, with an especial focus on vulnerability.Findings – Findings indicate that although the use of covert research is subject to substantial critique by apparently transgressing the often unquestioned moral legitimacy of informed consent, this carries ethical and practical utility for research related to safeguarding concerns. Arguably covert research enables research access to data likely to reveal abusive and oppressive practices.Research limitations/implications – Covert research assists in illuminating the hidden voices and lives of vulnerable people that may otherwise remain inaccessible. Such research needs to be subject to rigorous ethical standards to ensure that it is both justified and robust.Practical implications – Emphasising the need to consider all angles, questions and positions when addressing the social problem of adult protection and safeguarding.Originality/value – Increasingly social research is treated as being as potentially harmful as medical research. Ethics review tends towards conservative conformity, legitimising methodologies that may serve less social utility than other forms of investigation that privilege the safeguarding of vulnerable people.